Upaya Konservasi Pada Neonatus dengan Non-nutritive Sucking dan Pijat Ekstremitas: Conservation Efforts in Neonates with Non-nutritive Sucking and Extremity Massage - Halimah; Fajar Tri Waluyanti; Yeni Rustina (NERS Jurnal Keperawatan, 2016)
Pain is a discomfort sensational that felt by hospitalized neonates. The study use case study design of four babies who hospitalized in perinatology unit in RSAB Harapan Kita and Cipto Mangunkusumo hospital. The purpose of this case study is to analyze the fulfill comfort of neonates with NNS and extremities massage based on Levine Conservation Model application. The results is decrease neonates pain score with PIPP (Premature Infant Pain Profile), decrease in oxygen saturation changes, and heart rate changes in infants with invasive procedures. Although the fourth baby, no changes in pain scores with massage intervention extremities. Application of Levine Conservation Model in infants acute pain support for energy conservation, structural integrity, personal integrity, and social integrity. The study of pain management for neonates need to always be developed for support neonatal growth and development optimally.